Speech at Migration and the Global Development Agenda Conference - Kim, Jim Yong (World Bank, Washington, DC, 2019)
Jim Yong Kim, President of the World Bank Group, discussed the following topics. The Bank is helping many manage the humanitarian and development challenge. The Bank supports the global knowledge partnership on migration and development (KNOMAD), which helps countries develop evidence-based policy options and capacity to reap the benefits of migration. The future research agenda aims to build a database that identifies legal and policy restrictions that prevent countries from realizing migration’s possibilities and to develop approaches to education and social policy that facilitate migrants’ integration.